Synthesis and Antimicrobial Activity of Novel 2,4-Disubstituted Thiazoles - Nguyen Minh An1, Tran; Duk Lee1, Kap (Asian Journal of Chemistry, 2013)
A novel series of 2,4-disubtituted thiazole derivatives were synthesized. The structures of the compounds were established by IR, 1H, 13C NMR and mass spectroscopy. They were screened for antibacterial and antifungal activity against Bacillus megaterium, Bacillus cereus, Escherichia coli and Saccharomyces cerevisiae, Candida albicans, respectively.